The Production of Neutral N∗(11052) Resonance with Hidden Beauty from π-p Scattering - Chen Cheng; Xiao-Yun Wang (Advances in High Energy Physics)
We investigate the discovery potential of the predicted neutral hidden beauty N∗(11052) resonance through π-p scattering within an effective Lagrangian approach. Two reactions π-p→K-Σ+ and π-p→ηbn are studied in this work, with nucleon pole exchange as the background. It is found that the contributions of the N∗(11052) resonance give clear peak structures in the magnitude of 1 μb near the threshold of N∗(11052) in the total cross sections. The numerical results indicate that the center of mass energy W≃11–11.1 GeV would be the best energy window for searching the N∗(11052) resonance, where the N∗(11052) signal can be easily distinguished from the background. The COMPASS experiment at CERN’s Super Proton Synchrotron (SPS) with pion beam of ≃280 GeV will be an ideal platform for searching the super-heavy resonance with hidden beauty, which is promising for testing the theoretical results.